LEADERSHIP STYLES AND INNOVATION OUTCOMES: A META-ANALYTIC REVIEW ACROSS CULTURAL CONTEXTS - Abu Siri (ADISAM Publisher, 2026)
This study aims to comprehensively examine the relationship between leadership style and innovation outcomes through a meta-analytic approach based on a cross-cultural literature review. Organizational innovation is increasingly viewed as the result of a complex interaction between structural, individual, and leadership factors, particularly in a global environment characterized by diverse values, norms, and work practices. Through a systematic search of internationally reputable journal articles published over the past two decades, this study integrates empirical findings on the influence of various leadership styles, such as transformational, transactional, authentic, and participatory leadership, on various forms of innovation outcomes, including product innovation, process innovation, and employee innovative behavior. The results indicate that leadership styles oriented toward empowerment, vision, and psychological support tend to have a stronger and more consistent influence on innovation outcomes across cultural contexts, although the strength of the relationship varies depending on the dominant cultural values. These findings emphasize the importance of cultural sensitivity in applying leadership styles to foster innovation and provide a theoretical contribution to the development of cross-cultural leadership literature. Practically, the results of this study can serve as a reference for multinational organizations in designing adaptive and contextual leadership strategies to improve innovation performance.